Women in gender equality movement: a systematic literature review - Aulia, Syifa Siti; Marzuki,; Suyato,; Arpannudin, Iqbal (Frontiers in Sociology, 2024)
This study employs a rigorous Systematic Literature Review (SLR) methodology to examine the role of women’s leadership in advancing social movements for gender equality. Utilizing Scopus-indexed articles, we provide a comprehensive review of the relevant literature, analyzing factors contributing to the success of women leaders, effective leadership strategies, and the impacts of these efforts on communities and structural change. The findings indicate that women’s leadership plays a crucial role in fostering sustainable social change by enhancing women’s participation in decision-making, increasing public awareness of gender issues, and advocating for policies that promote gender equity. Additionally, this review identifies key challenges faced by women leaders in social movements, including gender stereotypes, institutional barriers, and inequities in resource access. In conclusion, strengthening women’s leadership in social movements is essential for advancing gender equality, though significant systemic obstacles must still be addressed to fully realize the transformative potential of such leadership.